Pemetaan Presentase Kepadatan Bangunan Menggunakan Model Regresi Berdasarkan Citra Landsat 8 - Rosyadi, Amri; Azahra, Maulidini Fatimah (Jurnal Penginderaan Jauh Indonesia, 2020)
The development of cities and the population causes an increasing number of buildings in an area. Building density identification can use relatively faster remote sensing imagery. This study aims to map the density of buildings in the city of Bandung based on the regression model. The method used to identify building density in this study is regression using the Normalized Difference Built-up Index (NDBI) index. The results of this study are regression models Y = 0.071 + 0.001X which can be used to map building densities with r square values at 0.383. This method is considered to be very fast and accurate compared to other methods for building density.